The relationship between advertising discourses and the expansion of EAD Higher Education in Alto Uruguai Gaúcho (Revista Contexto & Educação, 2025)
This article presents data from a study that sought to understand the legitimacy of education as a superior commodity, based on the expansion of distance education. In view of this, the formation of an educational market is taken into account in the investigative process, driven by the constitution of DE, as a factor that deepens the use of technology in higher education, and seeks to obtain its consolidation through the construction process of a social imaginary. Therefore, the theoretical-methodological approach of discourse analysis was undertaken in the movement of interpretation and analysis of advertising advertisements, in order to understand how different subjects are questioned by the institutions that choose this educational market. The research results reiterate the influence of advertising discourses on the questioning of subjects, given the incorporation of such discourses into the social imaginary, and the production of representations and meanings. This condition contributes to the legitimacy of education as a commodity, given that by acquiring private courses in the distance learning modality, subjects promote an action that directly impacts the expansion process.
Keywords: Commodity; Advertising speeches; Distance Education